Acute phase proteins in cats - Rosa,Rita Mourão (2019)
ABSTRACT: Acute phase proteins (APP) are proteins synthesized and released largely by hepatocytes upon the occurrence of cell damage or invasion by microorganisms. This article reviews the use of APP in feline diseases, identifying their usefulness in the clinical setting, analyzing 55 published papers. Serum amyloid A, alpha-1 acid glycoprotein, and haptoglobin are the indicators pointed out by the authors as useful in monitoring the acute inflammatory response in cats. Although, APP measurement is still not routinely used in veterinary medicine, together with clinical signs and other blood parameters, was of clinical interest and applicability in diseases such as feline infectious peritonitis, pancreatitis, renal failure, retroviral and Calicivirus infections. Although, there are commercially available kits for dosing feline APP, assay standardization aiming technical simplicity, more species specificity and with less associated costs will allow routine use in feline practice, as it is done in the human field.